2015
DOI: 10.1200/jco.2015.33.15_suppl.1561
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, hormone replacement therapy and breast cancer risk: A meta-analysis of prospective studies.

Abstract: Background: Lower risk of breast cancer has been reported among physically active women, but the risk in women using hormone replacement therapy (HRT) appears to be higher. We quantified the association between physical activity and breast cancer, and we examined the influence that HRT use and other risk factors had on this association. Methods: After a systematic literature search, prospective studies were meta-analysed using random-effect models applied on highest vs. lowest level of physical activity. Dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 15 publications
(15 reference statements)
2
15
1
1
Order By: Relevance
“…One cohort study, one nested case-control study and ten case-control studies showed that hypertension is associated with increased risk of breast cancer [63]. In addition, in our study, in contrast with literature, there was no signi cant association between the risk of breast cancer and either diabetes [64][65][66] or the physical activity [33,67] and or the smoking status [33,68]. But we found a signi cant association between the second-hand smoking and breast cancer, which shares similarity with ndings of Reynolds et al [69].…”
Section: Discussioncontrasting
confidence: 88%
“…One cohort study, one nested case-control study and ten case-control studies showed that hypertension is associated with increased risk of breast cancer [63]. In addition, in our study, in contrast with literature, there was no signi cant association between the risk of breast cancer and either diabetes [64][65][66] or the physical activity [33,67] and or the smoking status [33,68]. But we found a signi cant association between the second-hand smoking and breast cancer, which shares similarity with ndings of Reynolds et al [69].…”
Section: Discussioncontrasting
confidence: 88%
“…By comparison, we found no association between genetically determined, accelerometer-assessed physical activity and ER-breast cancer. In addition, we found no associations between genetically determined, self-reported physical activity and risks of breast or endometrial cancers.Our findings are largely consistent with previous prospective observational investigations of physical activity and risk of breast and endometrial cancers[4][5][6][7][8] . A large pooled analysis of 10 European and US cohort studies including 35,178 breast cancer cases reported a risk reduction of 10% comparing high versus low levels of self-reported physical activity (hazard ratio: 0.90; 95%: 0.87-0.93)22 .…”
supporting
confidence: 92%
“…The association between physical activity and risk of breast and endometrial cancers has received considerable attention in recent years, with umbrella reviews and meta-analyses of observational studies providing evidence for protective associations with both breast cancer [4][5][6] and endometrial cancer 2,6,7 . Those associations have been confirmed by reports of the World Cancer Research Fund 3 and the 2018 U.S.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations